Epistemologi Wakaf Keluarga: Pemahaman, Tanggung Jawab dan Pengelolaan Harta dalam Perspektif Ilmu Pengetahuan - Ghazy Triyatno; M. Lutfi Mustofa (Universitas Wahid Hasyim Semarang, 2024)
In recent times, discussions about waqf have been particularly engaging, particularly when they address the dynamic concepts involved in maintaining real estate growth. Previously, waqf problems were frequently associated with frozen and sluggish property. However, a number of improvements have since occurred. The numerous disputes over property management, which ultimately became a point of contention and led to land being abandoned, have resulted in the economic issue of family waqf property becoming a contentious one. This research project examines the intersection of family endowment (Wakaf keluarga) and epistemology within the context of contemporary social structures. The objective is to reconcile traditional religious beliefs with modern scientific perspectives on the understanding, obligations, and administration of family endowments. The study employs a conceptual analysis methodology to examine the interplay between family endowment and the epistemological foundations of science, elucidating their implications in social and religious contexts. This interdisciplinary approach enables the research to provide insights into the integration of epistemological principles into family endowment practices, with the aim of enhancing their effectiveness for the benefit of families and society as a whole. The findings underscore the necessity of synthesizing age-old values with contemporary knowledge paradigms to ensure the efficacious and sustainable stewardship of family endowments amidst the dynamism of the modern era. This study underscores the importance of bridging traditional and modern perspectives on family endowments, paving the way for enhanced welfare and sustainability in contemporary societies.Diskusi mengenai wakaf semakin menarik akhir-akhir ini, terutama ketika membahas konsep-konsep dinamis untuk mempertahankan pertumbuhan harta. Permasalahan wakaf sebelumnya sering dikaitkan dengan harta benda yang tetap dan lesu, namun kini telah banyak perbaikan yang terjadi. Karena banyaknya perselisihan mengenai pengelolaan harta benda yang akhirnya menjadi perdebatan dan berujung pada terlantarnya tanah, maka persoalan ekonomi harta wakaf keluarga pun menjadi salah satu yang kontroversial. Penelitian ini meneliti konvergensi wakaf keluarga dan epistemologi dalam kerangka sosial kontemporer. Penelitian ini bertujuan untuk menyelaraskan perspektif islam klasik dengan perspektif ilmiah modern mengenai pemahaman, kewajiban, dan administrasi wakaf keluarga. Dengan menggunakan metodologi analisis konseptual, penelitian ini mengkaji wakaf keluarga dengan landasan epistemologi ilmu pengetahuan, menjelaskan implikasi dalam lingkungan sosial dan keagamaan. Melalui lintas disiplin ilmu ini, penelitian berupaya memberikan wawasan tentang prinsip-prinsip epistemologi terhadap praktik wakaf keluarga untuk meningkatkan kesejahteraan keluarga dan masyarakat. Temuan penelitian menggarisbawahi pentingnya penggabungan nilai-nilai klasik dengan paradigma pengetahuan kontemporer untuk memastikan pengelolaan wakaf keluarga yang efektif dan berkelanjutan di tengah dinamika era modern. Penelitian ini menekankan pentingnya menjembatani pandangan tradisional dan modern tentang wakaf keluarga, membuka jalan bagi peningkatan kesejahteraan dan keberlanjutan di masyarakat kontemporer.